A first principles study of Ti2AlNb intermetallic. (February 2015) - Pathak, Ashish; Singh, A.K.
Abstract: Present work describes the structural stability and mechanical properties of the B2, D019 and O phases of Ti2 AlNb intermetallic using first principles density functional theory (DFT) within generalized gradient approximation (GGA). The equilibrium lattice constant values of the B2, D019 and O phases are in good agreement with the experimental data. Formation energy/atom of D019 and O phases are nearly close and significantly lower than that of the B2. Density of states also follow similar trend. The strong directional bonding between Ti–Nb atoms has been observed in O and D019 phases which is absent in B2. All the three phases satisfy stability criteria in terms of elastic constants and are associated with ductile behaviour based on G/B ratios. These phases reveal the presence of anisotropy however, the extent of anisotropy is very high for the B2 in comparison to those of the D019 and O phases. Highlights: E for of D019 and O phases are nearly close and significantly lower than the B2. The lattice constants of these phases are in good agreement with experimental data. The O and D019 phases show strong directional Ti–Nb bonding which is absent in B2 phase. All the three phases satisfy the stability criteria in terms of elastic constants. The extent of anisotropy is very high for the B2 in comparison to D019 and O phases. These phases exhibit ductile behaviour based on G/B ratios.